DETERMINANT OF STOCK PRICE INSURANCE COMPANY IN INDONESIA - Embun Prowanta; Indra Siswanti (The International Journal of Accounting and Business Society, 2021)
This study aims to analyze the effect of the Claim Expense Ratio and the Technical Reserve Ratio to the Stock Price with the Solvency Ratio as an intervening variable in insurance companies on the IDX. The populations in this research were all 12 insurance companies in Indonesia. The sampling criteria are insurance companies listed on the Indonesia Stock Exchange and publish quarterly financial reports continuously during the 2017-2018 period. There are 8 companies that meet the purposive sampling criteria. Data processing and analysis techniques are carried out using Path Analysis. The results show that the claim expense ratio has a significant positive effect on the solvency ratio, the technical reserve ratio has no effect on the solvency ratio, the claim expense ratio has a significant positive effect on stock prices, the technical reserve ratio has a significant negative effect on stock prices and the solvency ratio is not able to mediate the ratio of claim expense to stock prices and the solvency ratio is able to mediate the effect of the ratio of technical reserves to stock prices. Â  Keywords: Â The Claim Expense Ratio, The Technical Reserve Ratio, The Solvency Ratio, Stock Prices